2017
DOI: 10.1159/000479008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity Impairment Can Predict Postoperative Pulmonary Complications after Liver Transplantation

Abstract: Background: Postoperative respiratory complications (PRCs) are common after liver transplantation (LT) and contribute significantly to the related morbidity and mortality. Objective: The aim of this paper was to determine the incidence of PRCs after LT and the value of simple exercise capacity measures as independent predictors of PRCs. Methods: We conducted a prospective cohort study of consecutive adults submitted to LT at a University Hospital in Fortaleza Brazil from March 2013 to March 2015. At baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
1
19
0
4
Order By: Relevance
“…Therefore, any factor associated with dysfunction of normal lung endothelial-epithelial barriers or any other pulmonary abnormality is currently considered as a PPC in accordance with the broad diagnostic criteria [ 4 ]. In line with previous results [ 9 11 ], we also found that non-infectious pulmonary abnormalities, including pleural effusion and atelectasis, were the most frequent respiratory disorders after OLT. These non-infectious PPCs might be related to surgical maneuvers and have been reported to be usually self-limiting and respiratory physiotherapy might be unnecessary [ 6 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, any factor associated with dysfunction of normal lung endothelial-epithelial barriers or any other pulmonary abnormality is currently considered as a PPC in accordance with the broad diagnostic criteria [ 4 ]. In line with previous results [ 9 11 ], we also found that non-infectious pulmonary abnormalities, including pleural effusion and atelectasis, were the most frequent respiratory disorders after OLT. These non-infectious PPCs might be related to surgical maneuvers and have been reported to be usually self-limiting and respiratory physiotherapy might be unnecessary [ 6 , 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Postoperative pulmonary complications (PPCs) after orthotopic liver transplantation (OLT) – especially those occurring within the first month after surgery – are significantly associated with poor postoperative survival [ 1 ]. Using conventional broad criteria for diagnosis of PPCs, any postoperative pulmonary abnormality that adversely affects the clinical course of a patient could be defined as a PPC, including respiratory failure, pneumonia, atelectasis, pneumothorax, pleural effusion, acute lung injury (ALI), acute respiratory distress syndrome (ARDS), and various other forms of upper airway obstruction [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was a cross-sectional study of 100 adult ESLD patients undergoing pretransplantation assessment at a teaching hospital in Brazil between July 2015 and July 2017. Previous studies found correlations between exercise capacity and fatigue in chronic diseases (6,7) . This sample size calculation was based on the hypothesis that functional exercise capacity was at least well correlated with fatigue.…”
Section: Methodsmentioning
confidence: 91%
“…Patients with cirrhosis are reported to have significantly lower 6MWT values than individuals with stable chronic viral hepatitis, or healthy volunteers (5) . In a cohort study with 100 patients submitted to liver transplantation, Magalhães et al found 6MST and 6MWT to be associated with postoperative respiratory complications (6) .…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue has been listed as the most commonly experienced symptom in patients with chronic liver disease (5); it leads to complications, adversely affecting results of liver transplantation as well as survival (6,7). Ney et al reported that the level of physical activity which is reported by the subjects who have liver failure was low and the major barrier was fatigue (8).…”
Section: Introductionmentioning
confidence: 99%